The Effect of Termination Of Employee PT. Jakarta Phone 21 Pamekasan - Mohammad Amir Furqon Hayat; Achmarul Fajar; Akhmad Faishol Zaidani (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
The background problem of this research is when the researcher conducts a preliminary survey by becoming a buyer and while observing activies at PT Jakarta Phone 21 Pamekasan, there are some employees who are not as enthusiasthic in working as there are employees who only sit while pamobile phones even though there are buyers coming, employees who onlt offer goods without giving full information about products sold at that store. The purpose of this study is the first to determine the effect together the reasons for dismissal consisting of the company’s wishes and the desires of employees on the morale of PT, Jakarta Phone 21 Pamekasan. And to find out the most dominant variable influencing the morale of the employees of PT Jakarta Phone 21 Pamekasan.One theory that underlies the analysis of this research is Malayu Hasibuan's Theory which provides a definition of termination is the termination of a person's employee employment with a company organization. Data collection in this study was to use interviews and distribute questionnaires, as many as 27 questionnaires to respondents. From the validity test as many as 11 items, consisting of 3 items are invalid and 8 items are valid while the reliability test proved all the data instruments used in this study are reliable or reliable.In the first hypothesis with F test, the F count of 103.908 is greater than the F table of 3.40, then the first hypothesis is true that there is simultaneously the influence of the reasons for termination consisting of the company’s wishees and employees’ desires on the morale of the employeess of PT. Jakarta Phone 21 Pamekasan. In the second hypothesis using the t test, it is evident that the most dominant company desires affect the morale of the employees PT Jakarta Phone 21 Pamekasan amounted to 12.23 and the first hypothesis was accepted. Keyword: Company Desire; Employee's Desire and Employee's Spirit.